Optical films, optical laminates, functional glass and head-up displays
By using the barrier layer containing thermoplastic resin and the resin composition hardener of the ultraviolet hardening resin on the optical film, the problem of changes in the stability and phase difference value of the optical film in high temperature environment is solved, and higher durability and optical performance.
Patent Information
- Application Number
- CN202080057664.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-23
- Filing Date
- 2020-08-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-08-12
AI Technical Summary
The prior art is difficult to maintain the stable optical performance of the optical film under high temperature environments, and the phase difference value of the phase difference element varies greatly, affecting its durability and optical performance.
A barrier layer containing a thermoplastic resin is provided on the optical film, and a resin composition hardened with an ultraviolet hardening resin is formed to form a stable optical film structure to improve its durability and optical properties under high temperature environments.
It realizes the stable optical performance of the optical film under a high temperature environment, reduces the change in the phase difference value of the phase difference element, and improves the durability and overall performance of the optical film.
Smart Images

Figure CN114868048B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an optical film suitable for use in, for example, a head-up display, an optical laminate and functional glass using the optical film, and further to a head-up display using the same. Background Art
[0002] The method of displaying information to the driver of a car, airplane, etc. uses a navigation system, a head-up display (hereinafter also referred to as "HUD"), etc. HUD is a system that projects an image projected from an image projection unit such as a liquid crystal display (hereinafter also referred to as "LCD") onto, for example, the windshield of a car.
[0003] The light emitted from the image display unit is reflected by the reflector and then reflected on the windshield before reaching the observer. The observer views the image projected on the windshield, but the image is viewed at an image position farther from the windshield. In this method, the driver can obtain various information without having to move his or her sight while looking ahead of the windshield, so it is safer than the previous navigation system that requires moving the sight.
[0004] In the HUD system, the display information is actually projected overlapping with the scenery viewed from the windshield, but the display light is reflected from two surfaces of the windshield, the indoor side and the outdoor side, so the reflected image becomes a double image, making it difficult to see the display information.
[0005] Regarding this problem, it is known that the problem of reflected images becoming double images can be improved by using a phase difference element that can change the polarization direction by 90 degrees in the windshield for automobiles. For example, in Patent Document 1, it is disclosed that when display light formed into S polarization at the Brewster Angle is incident on the windshield for automobiles having a film-shaped optical rotation plate inside, a part of the S polarization is reflected on the surface of the windshield on the inside of the vehicle, and the S polarization that penetrates the surface is converted into P polarization by the optical rotation plate, and then all the P polarization is emitted to the outside of the vehicle on the surface of the windshield on the outside of the vehicle to prevent double images.
[0006] On the other hand, in the automotive windshield, etc., in order to make the phase difference element perform appropriate polarization conversion at a desired wavelength, the phase difference value of the phase difference element is important. However, this phase difference value has the problem of changing under various environmental conditions, such as high temperature environment, high temperature and high humidity environment, etc.
[0007] In order to solve this problem, a technology using a barrier layer that inhibits deterioration factors from reaching the light reflecting layer is disclosed in Patent Document 2. However, the durability (mainly heat resistance) required of the barrier layer, and the appearance and adhesion when formed into laminated glass are not disclosed in detail.
[0008] [Prior art literature]
[0009] [Patent Document]
[0010] [Patent Document 1] Japanese Patent Application Laid-Open No. 6-40271
[0011] [Patent Document 2] Japanese Patent Application Publication No. 2017-198981. Summary of the invention
[0012] [Problems to be solved by the invention]
[0013] An object of the present invention is to provide an optical film having excellent durability, little change in the phase difference value of a phase difference element under a high temperature environment, and capable of maintaining stable optical performance, as well as an optical laminate, functional glass, and a head-up display system using the optical film.
[0014] [Technical means to solve the problem]
[0015] The present inventors have conducted intensive studies to solve the above problems and have found that by providing a barrier layer containing a thermoplastic resin on an optical film, stable optical performance can be maintained even in a high temperature environment and the durability of the optical film is improved, thereby completing the present invention.
[0016] That is, the present invention relates to the following 1) to 14). 1)
[0018] An optical film comprising (A) an optical functional layer and (B) a barrier layer.
[0019] The barrier layer (B) comprises a cured product of a resin composition containing a (B-1) thermoplastic resin and a (B-2) ultraviolet curable resin. 2)
[0021] The optical film as described in 1) above, wherein the thermoplastic resin (B-1) is a polyvinyl acetal resin. 3)
[0023] The optical film as described in 1) or 2) above, wherein the (B-1) thermoplastic resin is a thermoplastic resin having a molecular weight of 10,000 to 60,000. 4)
[0025] The optical film as described in any one of 1) to 3) above, wherein the (B-1) thermoplastic resin is a polyvinyl acetal resin. 5)
[0027] The optical film as described in any one of 1) to 4) above, wherein the content of the (B-1) thermoplastic resin in the barrier layer is 1% by mass or more and 80% by mass or less. 6)
[0029] The optical film as described in any one of 1) to 5) above, wherein the (B-2) ultraviolet curable resin is a resin having a (meth)acryloyl group. 7)
[0031] The optical film as described in 6) above, wherein the resin having a (meth)acryloyl group is a (meth)acrylate epoxy resin. 8)
[0033] The optical film as described in any one of 1) to 7) above, wherein the glass transition temperature of the barrier layer (B) is 80° C. or higher and 300° C. or lower. 9)
[0035] The optical film as described in any one of 1) to 8) above, wherein the aforementioned (A) optical functional layer is any one of the following (A-1) to (A-4),
[0036] (A-1) 1 / 2 wavelength plate,
[0037] (A-2) 1 / 4 wavelength plate,
[0038] (A-3) A laminate of a half-wavelength plate and a circularly polarized light reflecting layer, and
[0039] (A-4) A laminate of a quarter-wave plate and a circularly polarized light reflecting layer. 10)
[0041] The optical film as described in 9) above, wherein the half-wavelength plate or the quarter-wavelength plate contains a polymerizable liquid crystal layer as a layer having a function of converting a polarization axis. 11)
[0043] The optical film as described in any one of 1) to 10) above, further comprising (C) a supporting substrate. 12)
[0045] An optical laminate comprising an interlayer laminated on the optical film according to any one of 1) to 11). 13)
[0047] A functional glass comprises the optical layered body described in 12) above and a glass plate. 14)
[0049] A head-up display system comprises: the optical film described in any one of 1) to 11), the optical layered body described in 12), or the functional glass described in 13), and an image display unit that emits display light for presenting an image display.
[0050] [Effects of the Invention]
[0051] According to the present invention, an optical film having excellent durability, little change in the phase difference value of a phase difference element under a high temperature environment, and capable of maintaining stable optical performance, as well as an optical laminate, functional glass, and a head-up display system using the optical film can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 FIG. 1 is a schematic diagram showing an embodiment of a head-up display system according to the present invention.
[0053] Figure 2 Schematic diagram showing other embodiments of the head-up display system according to the present invention.
[0054] Figure 3 The figure is a side cross-sectional view showing one embodiment of an optical film according to the present invention.
[0055] Figure 4 This is a side cross-sectional view showing one embodiment of the optical layered body according to the present invention.
[0056] Figure 5 The figure is a side cross-sectional view showing an embodiment of the functional glass according to the present invention. DETAILED DESCRIPTION
[0057] The following description will be made with reference to the accompanying drawings to explain embodiments according to the present invention. The following embodiments are merely examples of several representative embodiments of the present invention, and various modifications may be made within the scope of the present invention. In addition, in the following, the term "(meth)acryl" means "acryl" or "methacryl", for example, "(meth)acrylate" means "acrylate" or "methacrylate". In addition, the superscript "RTM" means a registered trademark.
[0058] The optical film of the present invention comprises (A) an optical functional layer and (B) a barrier layer. Figure 3 In one embodiment of the optical film of the present invention, the optical film 10 is formed into a structure in which an optical function layer 101 and a barrier layer 102 are stacked. Figure 3In the embodiment, the barrier layer 102 is laminated on one side of the optical functional layer 101, but the barrier layer 102 may be laminated on both sides of the optical functional layer 101. In addition, when the barrier layer 102 is laminated on one side of the optical functional layer 101, it is more preferred that a supporting substrate (C) described later is provided on the other side of the optical functional layer 101.
[0059] [(A) Optical functional layer]
[0060] The optical functional layer used in the present invention is not particularly limited as long as it has the function of converting the polarization axis of the incident light, and can be appropriately designed to obtain the desired polarized light. For example, a phase difference element such as a 1 / 2 wavelength plate or a 1 / 4 wavelength plate, a multilayer laminate of the phase difference element, or a laminate of a phase difference element and a circularly polarized light reflecting layer can be listed. Specifically, examples include: (A-1) a 1 / 2 wavelength plate, (A-2) a 1 / 4 wavelength plate, (A-3) a laminate of a 1 / 2 wavelength plate and a circularly polarized light reflecting layer, or (A-4) a laminate of a 1 / 4 wavelength plate and a circularly polarized light reflecting layer, but for example, when the optical film is used in the above-mentioned HUD system, it is more preferred to use a 1 / 2 wavelength plate.
[0061] In the case of using a 1 / 2 wavelength plate as an optical functional layer, the 1 / 2 wavelength plate has a phase difference element that converts P polarization into S polarization or S polarization into P polarization, that is, converts the polarization axis. For example, it can be obtained by uniaxially stretching a film composed of polycarbonate or cycloolefin polymer in such a way that the phase difference becomes 1 / 2 of the wavelength, or aligning the horizontally aligned polymerizable liquid crystal in thickness in such a way that the phase difference becomes 1 / 2 of the wavelength. Generally speaking, a 1 / 2 wavelength plate using a horizontally aligned polymerizable liquid crystal is composed of: a polymerizable liquid crystal layer as a layer having the function of converting the polarization axis, and a supporting substrate coated with a coating liquid forming the polymerizable liquid crystal layer. From the perspective of the orientation of the liquid crystal, the upper limit of the thickness of such a 1 / 2 wavelength plate is preferably less than 10 μm, and more preferably less than 5 μm. On the other hand, from the perspective of the polymerization of the liquid crystal, the lower limit of the thickness of this 1 / 2 wavelength plate is more preferably more than 0.3 μm, and more preferably more than 0.5 μm. In the case where light is incident from an oblique position relative to the main surface of the 1 / 2 wavelength plate, the phase difference sometimes changes due to the different incident angles of the light. In this case, in order to more strictly adapt the phase difference, for example, by using a phase difference element whose refractive index is adjusted, the change in the phase difference accompanying the incident angle can be suppressed. For example, when the refractive index of the phase difference element in the slow axis direction in the plane is set to nx, the refractive index of the phase difference element in the direction orthogonal to nx in the plane is set to ny, and the refractive index of the phase difference element in the thickness direction is set to nz, the coefficient Nz represented by the following formula (1) is preferably greater than 0.3 and less than 1.0, and is particularly preferably greater than 0.5 and less than 0.8.
[0062] Nz=(nx-nz) / (nx-ny) (1)
[0063] In the case where the optical film using the 1 / 2 wavelength plate is provided on the functional glass of the present invention described later, and the functional glass is applied to the HUD system, in order to effectively convert P polarization into S polarization or S polarization into P polarization in the HUD system, it is preferred to control the angle θ formed by the polarization axis of the S polarization or the polarization axis of the P polarization incident from a position inclined from 45° to 65° from the axis perpendicular to the surface of the functional glass and the slow axis of the 1 / 2 wavelength plate to be 35° to 47°. By making the incident angle of the S polarization or the P polarization incident on the 1 / 2 wavelength plate within the range of 45° to 65°, when the P polarization is incident on the functional glass, the reflectivity of the surface of the functional glass can be suppressed to less than 2% in theory. The P polarization after passing through is converted into S polarization by the 1 / 2 wavelength plate, and the converted S polarization is reflected at the interface between the functional glass and the air on the incident side and the reflection side. The reflected S polarized light is converted into P polarized light again by the 1 / 2 wavelength plate, and this P polarized light reaches the observer. In addition, when the S polarized light is incident on the functional glass, the S polarized light is reflected on the surface of the functional glass, and this S polarized light reaches the observer. A part of the S polarized light after passing through is converted into P polarized light by the 1 / 2 wavelength plate, and the converted P polarized light passes through without being reflected on the functional glass on the incident side and the reflection side or on the interface between the functional glass and the air. In this way, by controlling the incident angle of the S polarized light or the P polarized light incident on the functional glass, the generation of double images can be suppressed. In addition, when the angle θ is less than 35° or greater than 47°, the polarization axis conversion performance of converting the P polarized light incident on the functional glass into the S polarized light or converting the S polarized light into the P polarized light is low, resulting in a concern that the displayed image on the display also becomes dark. By appropriately controlling this angle θ, the 1 / 2 wavelength plate shows good polarization axis conversion performance, and as a result, the displayed image can be viewed more clearly.
[0064] In order to properly control the conversion performance of the polarization axis displayed by the 1 / 2 wavelength plate, the angle θ is preferably a value calculated by the following formulas (2) and (3). The technical significance of the following formulas (2) and (3) is explained here. When the S-polarized light or P-polarized light incident on the functional glass passes through the 1 / 2 wavelength plate having a medium different from air, the incident angle of the 1 / 2 wavelength plate changes. Here, the incident angle of the S-polarized light or P-polarized light relative to the functional glass is set to α, the actual incident angle on the 1 / 2 wavelength plate, that is, the refraction angle of the 1 / 2 wavelength plate is set to β, and the refractive index of air is set to n. α , let the refractive index of the half-wavelength plate be n βAccording to Snell's Law, sinα / sinβ=n β / n α Established, when this formula is simplified to an equation for obtaining β, formula (3) is derived. On the other hand, when the polarization axis of the S polarized light incident on the functional glass is set to the x-axis, the polarization axis of the P polarized light is set to the y-axis, and the angle formed by the y-axis and the slow axis of the 1 / 2 wavelength plate is set to θ, the phase difference value is Re, and through vectorial analysis, the y-axis is represented by Re·cosθ and the x-axis is represented by Re·sinθ. Here, it is known that the polarization axis conversion performance of the 1 / 2 wavelength plate is maximized when the light is incident at 45° relative to the slow axis of the 1 / 2 wavelength plate, so theoretically the incident angle relative to the slow axis of the 1 / 2 wavelength plate is preferably 45°. However, as mentioned above, even if the incident angle of the S polarized light or P polarized light incident on the functional glass is set to θ, the actual angle incident on the 1 / 2 wavelength plate is β. Therefore, for the y-axis of Re·cosθ (theoretical y-axis), when the y-axis (actual y-axis) tilted at an angle β with the x-axis as the center is obtained, Re·cosθ / actual y-axis=sin(90°-β), and the actual y-axis is represented by Re·cosθcosβ. In order to make the angle formed by the polarization axis of the S-polarized light or P-polarized light incident on the functional glass and the slow axis of the 1 / 2 wavelength plate become 45°, which is the more preferred angle of incidence, the x-axis (Re·sinθ) and the actual y-axis (Re·cosθcosβ) must be equal. Therefore, Re·sinθ=Re·cosθcosβ is obtained, and equation (2) is derived by simplifying this equation. In this way, by strictly controlling the angle θ based on the values calculated by the following equations (2) and (3) and in relation to the angle β actually incident on the 1 / 2 wavelength plate, the polarization axis conversion performance displayed by the 1 / 2 wavelength plate can be maximized.
[0065] tanθ=cosβ (2)
[0066]
[0067] θ: Angle between the slow axis of the half-wavelength plate and the polarization axis of S-polarized light or P-polarized light incident on the functional glass at any incident angle d
[0068] α: The incident angle of S-polarized light or P-polarized light relative to the functional glass
[0069] n α : Refractive index of air
[0070] n β : Refractive index of 1 / 2 wavelength plate
[0071] The range of the angle θ is preferably controlled within the range of ±5° of the value of the angle θ, and is particularly preferably controlled within the range of ±3°. When the angle θ is outside the range of ±5° of the angle that satisfies the values calculated by equations (2) and (3), the conversion efficiency of the polarization axis from P polarization to S polarization displayed by the 1 / 2 wavelength plate decreases. By controlling the range of the angle θ according to the values calculated by equations (2) and (3), the decrease in the conversion efficiency of the polarization axis from P polarization to S polarization performed by the 1 / 2 wavelength plate can be suppressed.
[0072] Substitute the refractive index of the 1 / 2 wavelength plate into the formula (3), set the refractive index of the 1 / 2 wavelength plate in the slow axis direction to nx, set the refractive index of the 1 / 2 wavelength plate in the direction orthogonal to nx in the plane to ny, set the refractive index of the 1 / 2 wavelength plate in the thickness direction to nz, and use the averaged sum of these values as the average refractive index. In addition, in the case of using a commercially available 1 / 2 wavelength plate, the average refractive index can also use the value recorded in the product catalog, etc. In addition, in the case of using the polymerizable liquid crystal described later as the material of the 1 / 2 wavelength plate, when using the original ordinary light refractive index no and extraordinary light refractive index ne of the liquid crystal, the average refractive index is expressed as (nx+ny+nz) / 3=(no+ne) / 2. When showing a specific example of θ calculated by formulas (2) and (3), for example, when the refractive index of air is set to 1.0, a 1 / 2 wavelength plate with a refractive index of 1.55 is used, and the incident angle of S-polarized light or P-polarized light is 45°, according to formulas (2) and (3), the value of θ is 42°, so the range of θ is more preferably 37° to 47°, and more preferably 39° to 45°. When the incident angle of S-polarized light or P-polarized light is 50°, according to formulas (2) and (3), the value of θ is 41°, so the range of θ is more preferably 36° to 46°, and more preferably 38° to 44°. In addition, when the incident angle of S-polarized light or P-polarized light is 56°, according to formulas (2) and (3), the value of θ is 40°, so the range of θ is more preferably 35° to 45°, and more preferably 37° to 43°. In addition, when the incident angle of S polarized light or P polarized light is 65°, according to formulas (2) and (3), the value of θ is 39°, so the range of θ is preferably 34° to 44°, and particularly preferably 36° to 42°. By controlling the angle θ formed by the polarization axis of S polarized light or P polarized light incident at a position inclined from 45° to 65° from the axis perpendicular to the surface of the functional glass and the slow axis of the 1 / 2 wavelength plate to be 35° to 47°, the 1 / 2 wavelength plate exhibits good polarization axis conversion performance, and as a result, a HUD system capable of viewing a displayed image more clearly can be provided.
[0073] As described above, in the present invention, by controlling the angle θ formed by the polarization axis of the P-polarized light or S-polarized light incident on the functional glass and the slow axis of the half-wave plate, the polarization axis conversion performance displayed by the half-wave plate can be further improved. In this case, from the viewpoint of the controllability of the slow axis of the half-wave plate and the production cost, it is more preferable to use a half-wave plate including a polymerizable liquid crystal layer as a layer having the function of converting the polarization axis.
[0074] The so-called polymerizable liquid crystal refers to a nematic liquid crystal monomer having a polymerizable group in the molecule and showing liquid crystal properties within a certain temperature range or concentration range. Examples of polymerizable groups include: (meth) acryloyl, vinyl, chalcone, cinnamoyl, and epoxy. In addition, in order to make the polymerizable liquid crystal show liquid crystal properties, it is more preferred to have a mesogen group in the molecule. The so-called mesogen group refers to a rod-shaped or plate-shaped substituent such as biphenyl, terphenyl, (poly) benzoic acid phenyl ester, (poly) ether, benzyl aniline or acenaphtho quinoxaline, or a disc-shaped substituent such as terphenyl, phthalocyanine or azacrown, that is, a group having the ability to induce liquid crystal phase action. Liquid crystal compounds with rod-shaped or plate-shaped substituents are called rod-shaped liquid crystals in the technical field. Examples of nematic liquid crystal monomers having such a polymerizable group include polymerizable liquid crystals described in Japanese Patent Application Laid-Open Nos. 2003-315556 and 2004-29824, polymerizable liquid crystals of the PALIOCOLOR series (manufactured by BASF) and the RMM series (manufactured by Merck). These nematic liquid crystal monomers having a polymerizable group may be used alone or in combination.
[0075] Furthermore, a polymerizable compound having no liquid crystallinity and capable of reacting with a nematic liquid crystal monomer having a polymerizable group may be added. Examples of such a compound include ultraviolet curable resins.Examples of the ultraviolet curable resin include dipentaerythritol hexa(meth)acrylate, a reaction product of dipentaerythritol penta(meth)acrylate and 1,6-hexamethylene diisocyanate, a reaction product of a triisocyanate having an isocyanuric acid ring and pentaerythritol tri(meth)acrylate, a reaction product of pentaerythritol tri(meth)acrylate and isophorone diisocyanate, dipentaerythritol penta(meth)acrylate, dipentaerythritol tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, di(trimethylolpropane) tetra(meth)acrylate, tri(acryloyloxyethyl) isocyanurate, and isophorone diisocyanate. tri(methacryloyloxyethyl)cyanurate, reaction product of glycerol triglycidyl ether and (meth)acrylic acid, tri(acryloyloxyethyl)isocyanurate modified with caprolactone, reaction product of trimethylolpropane triglycidyl ether and (meth)acrylic acid, triglycerol di(meth)acrylate, reaction product of propylene glycol diglycidyl ether and (meth)acrylic acid, polypropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, reaction product of 1,6-hexanediol diglycidyl ether and (meth)acrylic acid, 1,6-hexanediol di(meth)acrylate, glyceryl di(meth)acrylate, reaction product of ethylene glycol diglycidyl ether and (meth)acrylic acid, reaction product of diethylene glycol diglycidyl ether and (meth)acrylic acid, bis(acryloyloxyethyl)hydroxyethyl isocyanurate, bis(methacryloyloxyethyl)hydroxyethyl isocyanurate, reaction product of bisphenol A diglycidyl ether and (meth)acrylic acid, tetrahydrofurfuryl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate modified with caprolactone, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, polypropylene glycol (meth)acrylate, polyethylene glycol (meth)acrylate, phenoxyhydroxy (meth)acrylate Propyl ester, acryloyl morpholine, methoxy polyethylene glycol (meth)acrylate, methoxytetraethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxyethyl (meth)acrylate, glycidyl (meth)acrylate, glyceryl (meth)acrylate, ethyl carbitol (meth)acrylate, 2-ethoxyethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, 2-cyanoethyl (meth)acrylate, a reaction product of butyl glycidyl ether and (meth)acrylic acid, butoxytriethylene glycol (meth)acrylate, and butylene glycol mono(meth)acrylate, etc., can be used alone or in combination.These non-liquid crystal UV-curable resins must be added to a degree that does not cause the composition containing the nematic liquid crystal monomer to lose its liquid crystal properties, and are preferably added in an amount of 0.1 to 20 parts by mass, and particularly preferably 1.0 to 10 parts by mass, relative to 100 parts by mass of the nematic liquid crystal monomer having a polymerizable group.
[0076] When the nematic liquid crystal monomer having a polymerizable group and the polymerizable compound having no liquid crystal properties are ultraviolet curable, a photopolymerization initiator is added to cure the composition containing them by ultraviolet rays. Examples of photopolymerization initiators include: 2-methyl-1-[4-(methylthio)phenyl]-2-N-morpholinopropane-1-one (Irgacure manufactured by BASF Corporation); RTM 907), 1-hydroxycyclohexyl phenyl ketone (Irgacure RTM 184), 4-(2-hydroxyethoxy)-phenyl(2-hydroxy-2-propyl)ketone (Irgacure manufactured by BASF RTM 2959), 1-(4-dodecylphenyl)-2-hydroxy-2-methylpropane-1-one (Darocur RTM 953), 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one (Darocur RTM 1116), 2-hydroxy-2-methyl-1-phenylpropane-1-one (Irgacure RTM 1173) and acetophenone compounds such as diethoxyacetophenone; benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether and 2,2-dimethoxy-2-phenylacetophenone (Irgacure RTM 651) and other benzoin compounds; benzoylbenzoic acid, benzoylbenzoic acid methyl ester, 4-phenyldiphenyl ketone, hydroxydiphenyl ketone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3'-dimethyl-4-methoxydiphenyl ketone (Kayacure manufactured by Nippon Kayaku Co., Ltd. RTM MBP) and other diphenyl ketone (Benzophenone) compounds; and thioxanthone, 2-chlorothioxanthone (Nippon Kayaku Co., Ltd. Kayacure RTM CTX), 2-methylthioxanthone, 2,4-dimethylthioxanthone (Kayacure RTM RTX), isopropyl thioxanthone, 2,4-dichlorothioxanthone (Kayacure RTM CTX), 2,4-diethylthioxanthone (Kayacure RTMDETX) and 2,4-diisopropylthioxanthone (Kayacure RTM Thioxanthone compounds such as DITX and the like. Preferred photopolymerization initiators include, for example, Irgacure TPO, Irgacure TPO-L, Irgacure OXE01, Irgacure OXE02, Irgacure 1300, Irgacure 184, Irgacure 369, Irgacure 379, Irgacure 819, Irgacure 127, Irgacure 907, and Irgacure 1173 (all manufactured by BASF), and particularly preferably include Irgacure TPO, Irgacure TPO-L, Irgacure OXE01, Irgacure OXE02, Irgacure 1300, and Irgacure 907. These photopolymerization initiators may be used alone or in combination of a plurality of types at any ratio.
[0077] When a phenyl ketone compound or a thioxanthone compound is used as a photopolymerization initiator, an auxiliary agent may be used in combination to promote the photopolymerization reaction. Examples of the auxiliary agent include amine compounds such as triethanolamine, methyldiethanolamine, triisopropanolamine, n-butylamine, N-methyldiethanolamine, diethylaminoethyl methacrylate, Michler's Ketone, 4,4'-diethylaminobenzophenone, ethyl 4-dimethylaminobenzoate, (n-butoxy)ethyl 4-dimethylaminobenzoate, and isopentyl 4-dimethylaminobenzoate.
[0078] The content of the photopolymerization initiator and the auxiliary agent is preferably used within a range that does not affect the liquid crystallinity of the composition, and the amount is preferably 0.5 to 10 parts by mass, and particularly preferably 2 to 8 parts by mass, relative to 100 parts by mass of the compound cured by ultraviolet rays in the composition. In addition, the auxiliary agent is preferably 0.5 to 2 times the amount of the photopolymerization initiator.
[0079] At least one compound selected from the group consisting of a compound represented by the following formula (4), a compound represented by the following formula (5) and a compound represented by the following formula (6) (hereinafter referred to as simply "additive compound"), by being added together with a liquid crystal compound, can further enhance the heat resistance of the half wavelength plate and further reduce the change in the phase difference value of the half wavelength plate even in a high temperature environment.
[0080]
[0081]
[0082] In formula (4) to formula (6), R 1-1 , R 1-2 and R 1-3 Each independently represents an alkyl group having a branched structure with 5 or more carbon atoms. 1-1 , R 1-2 and R 1-3 When each independently is an alkyl group having a branched structure, the change in the phase difference value of the half-wavelength plate under a high temperature environment is particularly small. The carbon number is preferably 6 or more and 18 or less. 1-1 , R 1-2 and R 1-3 Particularly preferably, each independently is CH3-(CH2) m -CHRX- group. Here, RX represents an alkyl group having 1 to 5 carbon atoms, and R 1-1 , R 1-2 and R 1-3 More preferably, each independently is CH3-(CH2) m -CH(C2H5)- group, particularly preferably 2-ethylhexyl or 2-ethylbutyl. Here, m represents an integer in the range of 1 to 6. In formula (5), R 3 Represents -(CH2) p -yl or phenylene, p represents an integer from 4 to 8. 3 In the case of a phenylene group, the phenylene group may have a substituent at any of the ortho, meta, and para positions, but preferably has a substituent at the ortho position. 4 represents a substituted phenylene group, and the substituted phenylene group may have a substituent at any of the ortho, meta, and para positions, but preferably has a substituent at the ortho and para positions. 2 It represents a -CH2-CH2- group, a -CH2-CH(CH3)- group or a -CH2-CH2-CH2- group, and is more preferably a -CH2-CH2- group.
[0083] Examples of the compound represented by formula (4) include triethylene glycol di-2-ethylhexanoate (3GO), tetraethylene glycol di-2-ethylhexanoate (4GO), triethylene glycol di-2-ethylbutyrate (3GH), tetraethylene glycol-di-ethylbutyrate, pentaethylene glycol-di-ethylhexanoate, octaethylene glycol-di-ethylhexanoate, nonaethylene glycol-di-2-ethylhexanoate and decaethylene glycol-di-2-ethylhexanoate.
[0084] Examples of the compound represented by formula (5) include bis(2-ethylhexyl) adipate, bis(2-ethylhexyl) azelaic acid, bis(2-ethylbutyl) azelaic acid, di-2-ethylhexyl sebacate, di-2-ethylbutyl sebacate, di-2-ethylhexyl phthalate, and di-2-ethylbutyl phthalate.
[0085] Examples of the compound represented by formula (6) include trimellitic acid tri-2-ethylhexyl ester and trimellitic acid tri-2-ethylbutyl ester.
[0086] The compound represented by formula (4), the compound represented by formula (5), and the compound represented by formula (6) can be used alone or in combination of two or more. Among these, the compound represented by formula (4) has excellent compatibility with the above-mentioned liquid crystal compound, and a stable phase difference element can be obtained, so it is more preferred. Among the compounds represented by formula (4), from the perspective of excellent compatibility with the above-mentioned liquid crystal compound and the excellent effect of suppressing the change of the phase difference value of the 1 / 2 wavelength plate under a high temperature environment, triethylene glycol di-2-ethylhexanoate (3GO), tetraethylene glycol di-2-ethylhexanoate (4GO) and triethylene glycol di-2-ethylbutyrate (3GH), more preferably triethylene glycol di-2-ethylhexanoate (3GO).
[0087] The content of at least one additive compound selected from the group consisting of the compound represented by formula (4), the compound represented by formula (5) and the compound represented by formula (6) is not particularly limited, and is preferably 0.1 to 300 parts by mass, particularly preferably 0.5 to 50 parts by mass, more preferably 0.8 to 30 parts by mass, particularly preferably 1 to 15 parts by mass, relative to 100 parts by mass of the liquid crystal compound. When the content of the additive compound is less than 0.1 parts by mass, the effect of suppressing the change of the phase difference value of the 1 / 2 wavelength plate in a high temperature environment may not be obtained. On the other hand, even if the content of the additive compound exceeds 300 parts by mass, the effect of suppressing the change of the phase difference value of the 1 / 2 wavelength plate in a high temperature environment does not change, so from the perspective of material cost, the upper limit of the content of the additive compound is preferably 300 parts by mass or less.
[0088] In response to the design of the HUD system, a quarter wavelength plate can also be used as an optical functional layer. The quarter wavelength plate is a phase difference element having the function of converting circular polarization into linear polarization. For example, it can be obtained by uniaxially stretching a film composed of polycarbonate or cycloolefin polymer in such a way that the phase difference becomes 1 / 4 of the wavelength, or by aligning the horizontally aligned polymerizable liquid crystal in thickness in such a way that the phase difference becomes 1 / 4 of the wavelength. In addition, the quarter wavelength plate preferably contains the above-mentioned polymerizable liquid crystal layer. In this case, the quarter wavelength plate is composed of: the above-mentioned polymerizable liquid crystal layer as a layer having the function of converting the polarization axis, and a supporting substrate coated with a coating liquid forming the polymerizable liquid crystal layer.
[0089] In the case where the phase difference caused by wavelength dispersion is greatly deviated, a phase difference element called a broadband quarter-wave plate can be used for the quarter-wave plate. The so-called broadband quarter-wave plate is a phase difference element after the wavelength dependence of the phase difference is reduced. For example, it can be listed as: a phase difference element in which a half-wave plate and a quarter-wave plate with the same wavelength dispersion are stacked in such a way that the angle formed by each slow axis becomes 60°, and a polycarbonate-based phase difference element (made by Teijin: Pure Ace WR-S) after the wavelength dependence of the phase difference is reduced. In addition, in the case where the incident angle of light is obliquely incident with respect to the quarter-wave plate, such as in a HUD, the phase difference sometimes changes due to the difference in the phase difference element due to the difference in the incident angle of the light. In this case, a method of more strictly matching the phase difference can, for example, suppress the change in the phase difference accompanying the incident angle by using a phase difference element after the refractive index of the phase difference element is adjusted. In this example, when the refractive index of the phase difference element in the slow axis direction within the plane is set to nx, the refractive index of the phase difference element in the direction orthogonal to nx within the plane is set to ny, and the refractive index of the phase difference element in the thickness direction is set to nz, the coefficient Nz represented by the above formula (1) is preferably controlled to be 0.3 to 1.0, and particularly preferably 0.5 to 0.8.
[0090] In the case where the optical film using such a quarter wavelength plate is set on the functional glass of the present invention described later, and the functional glass is applied to the HUD system, the optical functional layer is preferably a laminate of a quarter wavelength plate and a circularly polarized light reflecting layer. Specifically, it is preferably composed of: a circularly polarized light reflecting layer, a first quarter wavelength plate stacked on one side of the circularly polarized light reflecting layer, and a second quarter wavelength plate stacked on the other side of the circularly polarized light reflecting layer. The circularly polarized light reflecting layer can preferably use a light reflecting layer using cholesterol liquid crystal. In the case of such a structure, in the HUD system, among the two quarter wavelength plates, the first quarter wavelength plate is set on the side where the S polarized light or the P polarized light is incident, and the second quarter wavelength plate is set on the side where the circularly polarized light after passing through the circularly polarized light reflecting layer is incident. For example, in the case where the circularly polarized light reflecting layer has a right circularly polarized light reflecting function, when the P polarized light is incident on the first quarter wavelength plate, at the interface of the first quarter wavelength plate, the P polarized light is almost not reflected and penetrates the first quarter wavelength plate. The transmitted P-polarized light is converted into right circularly polarized light by the first quarter wavelength plate, and this right circularly polarized light is reflected by the circularly polarized light reflecting layer due to the right circularly polarized light conversion performance of the circularly polarized light reflecting layer. The reflected right circularly polarized light is converted into the original P-polarized light again by the first quarter wavelength plate, and this P-polarized light reaches the observer. In addition, the right circularly polarized light that is not reflected by the circularly polarized light reflecting layer but passes through the circularly polarized light reflecting layer passes through the second quarter wavelength plate and returns to the original P-polarized light, and this P-polarized light passes through the interface on the outside of the second quarter wavelength plate without being reflected. On the other hand, even in the case where S-polarized light is incident on the first quarter wavelength plate, the S-polarized light is reflected on the surface of the first quarter wavelength plate, and this S-polarized light reaches the observer. The S-polarized light that is not reflected by the first quarter wavelength plate but passes through the first quarter wavelength plate is converted into left circularly polarized light by the first quarter wavelength plate. This left circularly polarized light is not reflected on the circularly polarized light reflecting layer having the function of reflecting right circularly polarized light, but passes through the circularly polarized light reflecting layer, and returns to the original S polarized light through the second 1 / 4 wavelength plate. This S polarized light is also almost not reflected on the interface outside the second 1 / 4 wavelength plate, but passes through. Even in the case where the circularly polarized light reflecting layer has the function of reflecting left circularly polarized light, the P polarized light or S polarized light reaches the observer through the same principle.
[0091] From the viewpoint of the orientation of the liquid crystal, the upper limit of the thickness of the 1 / 4 wavelength plate is preferably less than 10 μm, and more preferably less than 5 μm. On the other hand, the lower limit of the thickness of the 1 / 4 wavelength plate is more preferably more than 0.3 μm, and more preferably more than 0.5 μm. In addition, from the viewpoint of the orientation of the liquid crystal, the upper limit of the thickness of the circularly polarized light reflecting layer is more preferably less than 10 μm, and more preferably less than 5 μm. On the other hand, from the viewpoint of the polymerization of the liquid crystal, the lower limit of the thickness of the circularly polarized light reflecting layer is more preferably more than 0.3 μm, and more preferably more than 0.5 μm.
[0092] In the optical film of the present invention, (A) optical functional layer can be provided with more than 2 layers. In this case, other layers may not be used between the optical functional layers, that is, each optical functional layer may be directly stacked, but it is more preferred to provide a bonding layer using an adhesive between the optical functional layers. The adhesive may include an acrylic or rubber adhesive, and an acrylic adhesive that is easy to adjust the bonding property, holding power, etc. may be more preferred. The adhesive may include an ultraviolet curing resin composition, a thermosetting resin composition, and a mixture thereof. In the case of an ultraviolet curing resin composition, in the presence of a photopolymerization initiator, the composition mixed with a plurality of monomers having an acryl group or an epoxy group is irradiated with ultraviolet light to harden it, thereby bonding the optical functional layers. In the case of a thermosetting resin composition, in the presence of an acid catalyst, the composition mixed with a plurality of monomers having an epoxy group is heated to harden it, thereby bonding the optical functional layers. Alternatively, a composition composed of a plurality of monomers or polymers having an amino group, a carboxyl group, or a hydroxyl group may be heated and cured in the presence of a compound having an isocyanate group or melamine, thereby bonding the optical functional layers.
[0093] [(B) Barrier layer]
[0094] In the optical film of the present invention, the (B) barrier layer has: a cured product (cured film) of a resin composition (hereinafter also referred to as "resin composition for barrier layer formation") containing (B-1) a thermoplastic resin and (B-2) an ultraviolet curable resin. By providing a barrier layer containing a thermoplastic resin on the optical film, the phase difference element provided as the (A) optical functional layer can be protected from degradation factors. In addition, the durability of the optical film having such a barrier layer is mainly excellent in the hue change (ΔE) after the heat resistance test, and the appearance and tightness when the optical film is used to form a laminated glass are also excellent. Therefore, it has high durability in a high temperature environment, especially high heat resistance, and can provide an optical film that can suppress the change in the phase difference value of the phase difference element for a long period of time. Moreover, the barrier layer can be a single layer or a stack of two or more layers.
[0095] [(B-1) Thermoplastic resin]
[0096] (B-1) Thermoplastic resin is not particularly limited, as long as it is a thermoplastic resin that can be formed by heating. Such thermoplastic resins include, for example, polyvinyl acetal resin, high-density polyethylene resin, low-density polyethylene resin, linear low-density polyethylene resin, ultra-low-density polyethylene resin, polypropylene resin, polybutadiene resin, cyclic olefin resin, polymethylpentene resin, polystyrene resin, ethylene-vinyl acetate copolymer, ionomer resin, ethylene-vinyl alcohol copolymer resin, ethylene-ethyl acrylate copolymer, acrylonitrile-styrene resin, acrylonitrile-chlorinated polystyrene-styrene copolymer resin, acrylonitrile-acrylic rubber-styrene copolymer resin, acrylonitrile-butadiene-styrene copolymer resin, acrylonitrile-EPDM-styrene copolymer resin, silicone rubber-acrylonitrile-styrene copolymer resin, cellulose-acetate-butyrate resin, cellulose acetate resin, methacrylic resin, ethylene-methyl methacrylate copolymer resin, ethylene-ethyl acrylate resin, vinyl chloride resin, chlorinated polyethylene resin, polytetrafluoroethylene resin, Fluorinated vinyl resin, tetrafluoroethylene-hexafluoropropylene copolymer resin, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer resin, tetrafluoroethylene-ethylene copolymer resin, polychlorotrifluoroethylene resin, polyvinylidene fluoride resin, nylon 4,6, nylon 6, nylon 6,6, nylon 6,10, nylon 6,12, nylon 12, nylon 6T, nylon 9T, aromatic nylon resin, polyacetal resin, ultra-high molecular weight polyethylene resin, polybutylene terephthalate resin, polyethylene terephthalate diester resin, polyethylene naphthalate resin, amorphous copolyester resin, polycarbonate resin, modified polyphenylene ether resin, thermoplastic polyurethane elastomer, polyphenylene sulfide resin, polyetheretherketone resin, liquid crystal polymer, polytetrafluoroethylene resin, polyfluoroalkoxy resin, polyetherimide resin, polysulfone resin, polyketone resin, thermoplastic polyimide resin, polyamideimide resin, polyarylate resin, polysulfone resin, polyethersulfone resin, biodegradable resin, biomass resin, etc. The thermoplastic resin can be used alone or in combination of two or more.
[0097] Examples of commercially available thermoplastic resins include: (S-LEC RTM BL-1, BL-1H, BL-2, BL-2H, BL-5, BL-10, BL-S, BL-L, BM-1, BM-2, BM-5, BM-S, BH-3, BH-6, BH-S, BX-1, BX-1, BX-5, KS-10, KS-1, KS-3, KS-5 (all manufactured by Sekisui Chemical Co., Ltd.); Vylon of amorphous polyester resin and crystalline polyester resin RTM Vylonal series, water-dispersible polyester resin RTM Series, polyester urethane resin Vylon RTM UR series, Vyloecol of amorphous polylactic acid resinRTM series (all manufactured by Toyobo Co., Ltd.); Septon, a styrene elastomer RTM Series, Hybrar RTM Series, Kurarity of acrylic block copolymers RTM Earneston series, thermoplastic elastomer compounds RTM Series, isoprene-based Kuraprene RTM series (all manufactured by Kuraray); Denka Poval of polyvinyl alcohol RTM series (manufactured by Denka); YS Resin of terpene resin RTM PX Series, YS Resin RTM PXN series, YS Resin of aromatic modified terpene resin RTM TO series (all manufactured by Yasuhara Chemical Co., Ltd.); and YS Polyster of terpene phenol resin RTM U, YS Polyster RTM T. YS Polyster RTM S, YS Polyster RTM G. YSPolyster RTM N.YS Polyster RTM K. YS Polyster RTM TH (all manufactured by Yasuhara Chemical Co., Ltd.) and the like.
[0098] Among these, polyvinyl acetal resin is more preferred from the viewpoints of appearance and adhesion when using the optical film to constitute laminated glass, hue change (ΔE) before and after the heat resistance test, and optical properties before and after the heat resistance test. The so-called polyvinyl acetal resin refers to a resin obtained by reacting aldehyde with polyvinyl alcohol, and is a compound represented by the following formula (7).
[0099]
[0100] In formula (7), R represents C1 to C 10 The straight chain, branched or cyclic alkyl group is preferably a C1 to C6 straight chain alkyl group, more preferably a C1 to C4 straight chain alkyl group, particularly preferably C1, that is, a methyl group (polyvinyl acetal resin), or C4, that is, a n-butyl group (polyvinyl butyral resin), and most preferably a methyl group. When R is a methyl group, that is, when the thermoplastic resin is a polyvinyl acetal resin, the hue change before and after the heat resistance test is small, and the practicality is high.
[0101] In the above formula (7), n represents the number of repeating units, and is more preferably 50 or more and 1500 or less. The upper limit of n is particularly preferably 1000, more preferably 800, particularly preferably 600, and most preferably 200. In addition, the lower limit of n is particularly preferably 70, more preferably 100, particularly preferably 120, and most preferably 150.
[0102] In addition, the more preferred molecular weight (weight average molecular weight: Mw) of the thermoplastic resin is 6,000 or more and 1,000,000 or less. The upper limit of the molecular weight is particularly preferably 120,000, more preferably 96,000, particularly preferably 60,000, and most preferably 20,000. In addition, the lower limit of the molecular weight is particularly preferably 8,500, more preferably 10,000, particularly preferably 12,000, and most preferably 16,000. That is, the molecular weight of the thermoplastic resin is most preferably 10,000 or more and 60,000 or less. The above weight average molecular weight is measured by gel permeation chromatography (GPC: Gel Permeation Chromatography).
[0103] The content of the thermoplastic resin in the barrier layer is 1% by mass or more and 80% by mass or less, which is one of the more preferred solutions. The upper limit of the content of the thermoplastic resin in the barrier layer is particularly preferably 50% by mass, more preferably 40% by mass, and particularly preferably 30% by mass. In addition, the lower limit of the content of the thermoplastic resin in the barrier layer is particularly preferably 2% by mass, more preferably 5% by mass, and particularly preferably 10% by mass. That is, the content of the thermoplastic resin in the barrier layer is most preferably 10% by mass or more and 30% by mass or less.
[0104] [(B-2) Ultraviolet curable resin]
[0105] (B) The barrier layer has (B-2) an ultraviolet curable resin. The ultraviolet curable resin includes, for example, resins having a vinyl group, a vinyl ether group, an allyl group, a maleimide group, a (meth)acryloyl group, and the like. Among them, from the viewpoint of reactivity and versatility, the ultraviolet curable resin is preferably a resin having a (meth)acryloyl group, for example, a (meth)acrylate compound. The ultraviolet curable resin may be used alone or in combination of two or more.
[0106] Examples of the resin having a (meth)acryloyl group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 1,4-butylene glycol mono(meth)acrylate, carbitol (meth)acrylate, acryloyl morpholine, a half ester of a reaction product of a hydroxyl-containing (meth)acrylate and an acid anhydride of a polycarboxylic acid compound, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane polyethoxy tri(meth)acrylate, glycerol polypropoxy tri(meth)acrylate, and di(meth)acrylate of an ε-caprolactone adduct of hydroxypivalate neopentyl glycol (e.g., manufactured by Nippon Kayaku Co., Ltd., KAYARAD RTM HX-220, HX-620, etc.), pentaerythritol tetra(meth)acrylate, poly(meth)acrylate of the reaction product of dipentaerythritol and ε-caprolactone, poly(meth)acrylate dipentaerythritol (e.g., Nippon Kayaku Co., Ltd., KAYARAD RTM DPHA, etc.), (meth)acrylate epoxy esters of the reaction products of mono- or poly-glycidyl compounds and (meth)acrylic acid, etc. Among these, (meth)acrylate epoxy esters are most suitable.
[0107] The glycidyl compound used for the (meth)acrylate epoxy ester of the reaction product of a mono- or poly-glycidyl compound and (meth)acrylic acid is not particularly limited, and examples thereof include bisphenol A, bisphenol F, bisphenol S, 4,4'-biphenol, tetramethylbisphenol A, dimethylbisphenol A, tetramethylbisphenol F, dimethylbisphenol F, tetramethylbisphenol S, dimethylbisphenol S, tetramethyl-4,4'-bisphenol, dimethyl-4,4'-biphenol, 1-(4-hydroxyphenyl)-2-[4-(1,1-bis-(4-hydroxyphenyl)ethyl)phenyl]propane, 2,2 Glycidyl ethers of polyphenols such as '-methylene-bis(4-methyl-6-tert-butylphenol), 4,4'-butylene-bis(3-methyl-6-tert-butylphenol), trihydroxyphenylmethane, resorcinol, hydroquinone (also known as hydroquinone), pyrogallol, phenols having a diisopropylidene skeleton, phenols having a fluorene skeleton such as 1,1-di-4-hydroxyphenylfluorene, phenolated polybutadiene, brominated bisphenol A, brominated bisphenol F, brominated bisphenol S, brominated phenol novolac, brominated cresol novolac, chlorinated bisphenol S, and chlorinated bisphenol A.
[0108] The (meth) acrylic acid epoxy ester of the reaction product of these mono- or poly-glycidyl compounds and (meth) acrylic acid can be obtained by subjecting an equivalent amount of (meth) acrylic acid to an esterification reaction on the epoxy group. This synthesis reaction can be carried out by a generally known method. For example, in resorcinol diglycidyl ether, the equivalent amount of (meth) acrylic acid is added together with a catalyst (for example, benzyldimethylamine, triethylamine, benzyltrimethylammonium chloride, triphenylphosphine, triphenylstilbene, etc.) and a polymerization inhibitor (methoquinone, hydroquinone, methylhydroquinone, phenothiazine, dibutylhydroxytoluene, etc.), and the esterification reaction is carried out at, for example, 80 to 110° C. The (meth) acrylated resorcinol diglycidyl ether obtained in this way is a resin having a (meth) acryloyl group that is free radical polymerizable. In addition, it is particularly preferred in the case of an adhesive resin having both a polar functional group and two or more (meth) acryloyl groups in the molecule.
[0109] In addition, the resin having a (meth)acryloyl group is particularly preferably an adhesive resin having a polar functional group and two or more (meth)acryloyl groups in the molecule. The so-called polar functional group includes, for example, hydroxyl, carboxyl, phosphorus, amino, imino, carbamoyl, cyano, isocyanate, nitro, nitroso, hydrazine, ureido, guanidino, sulfhydryl, sulfinyl, sulfonic acid, furyl, thienyl, pyrrolyl, pyrrolidinyl, pyridyl, pyrrolidino, piperidinyl, N-morpholino, quinolyl, etc. In addition, the polar functional group may be substituted by an alkyl group or an alkoxy group. Furthermore, a polar bonding site different from a substituent such as a urethane bond, an ether bond, an ester bond (excluding the ester bond in a (meth)acryloyl group) may be included as a polar functional group.
[0110] Examples of binder resins having two or more polar functional groups and having both a (meth)acryloyl group and a polar functional group include pentaerythritol triacrylate (KAYARAD RTM PET-30, manufactured by Nippon Kayaku Co., Ltd.), a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (KAYARAD RTMDPHA, manufactured by Nippon Kayaku Co., Ltd.), 2-hydroxy-3-acryloyloxypropyl methacrylate (701A, manufactured by Shin-Nakamura Chemical Co., Ltd.), ethoxylated isocyanuric acid triacrylate (A-9300, manufactured by Shin-Nakamura Chemical Co., Ltd.), ε-caprolactone-modified tri-(2-acryloyloxyethyl) isocyanurate (A-9300-1CL, manufactured by Shin-Nakamura Chemical Co., Ltd.); (meth)acrylate monomer compounds such as bisphenol A type epoxy acrylate (R-115F, R-130, R-381, etc., manufactured by Nippon Kayaku Co., Ltd.), bisphenol F type epoxy acrylate (ZFA-266H, manufactured by Nippon Kayaku Co., Ltd.), acid-modified epoxy acrylate (ZAR series, ZF R series, ZCR series, Nippon Kayaku Co., Ltd.), etc. acrylic epoxy esters; and polyester urethane acrylates (UX3204, UX-4101, UXT-6100, Nippon Kayaku Co., Ltd.), mixed urethane acrylates (UX-6101, UX-8101, Nippon Kayaku Co., Ltd.), polyether urethane acrylates (UX-937, UXF-4001-M35, Nippon Kayaku Co., Ltd.), ester urethane acrylates (DPHA-40H, UX-5000, UX-5102D-M20, UX-5103D, UX-5005, Nippon Kayaku Co., Ltd.), etc.
[0111] The ultraviolet curable resin is preferably an adhesive resin having 2 or more and 9 or less (meth)acryloyl groups and polar functional groups, and more preferably an adhesive resin having 3 or more and 6 or less (meth)acryloyl groups and polar functional groups. When the number of the reactive (meth)acryloyl groups is 10 or more, the obtained cured product is too rigid, which may lead to a decrease in bonding strength.
[0112] In the barrier layer, the content of the ultraviolet curable resin is preferably 10% by mass or more and 99% by mass or less. The upper limit of the content of the ultraviolet curable resin is preferably 95% by mass, more preferably 90% by mass, and particularly preferably 85% by mass. In addition, the lower limit of the ultraviolet curable resin is preferably 20% by mass, more preferably 50% by mass, and particularly preferably 75% by mass. That is, the content of the ultraviolet curable resin is most preferably 75% by mass or more and 85% by mass or less.
[0113] The barrier layer may further contain a radical polymerization initiator for curing the ultraviolet curable resin. The radical polymerization initiator refers to a photoradical polymerization initiator and / or a thermal radical polymerization initiator.
[0114] The photo-radical polymerization initiator is not particularly limited as long as it is a compound that generates free radicals or acids by ultraviolet irradiation and initiates a chain polymerization reaction. Examples thereof include: benzyl dimethyl ketal, 1-hydroxycyclohexyl phenyl ketone, diethylthioxanthone, diphenyl ketone, 2-ethyl anthraquinone, 2-hydroxy-2-methylethyl phenyl ketone, 2-methyl-[4-(methylthio)phenyl]-2-N-morpholinyl-1-propane, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, camphorquinone, 9-fluorenone, diphenyl disulfide, etc. Specific examples thereof include: IRGACURE RTM 651, 184, 2959, 127, 907, 369, 379EG, 819, 784, 754, 500, OXE01, OXE02, DAROCURE RTM 1173, LUCIRIN RTM TPO (both manufactured by BASF), SEIKUOL RTM Z, BZ, BEE, BIP, BBI (all manufactured by Seiko Chemical Co., Ltd.), etc.
[0115] When a photoradical polymerization initiator is used, the content is preferably 0.01 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the total amount of the ultraviolet curable resin. The upper limit of the content of the photoradical polymerization initiator is particularly preferably 7 parts by mass, more preferably 5 parts by mass, particularly preferably 4 parts by mass, and most preferably 3 parts by mass. In addition, the lower limit of the photoradical polymerization initiator is particularly preferably 0.01 parts by mass, more preferably 0.1 parts by mass, particularly preferably 1 parts by mass, and most preferably 1.5 parts by mass.
[0116] The thermal free radical polymerization initiator is not particularly limited as long as it is a compound that generates free radicals by heating and initiates a chain polymerization reaction. Examples thereof include organic peroxides, azo compounds, benzoin compounds, benzoin ether compounds, acetophenone compounds, benzopinacol, etc., with benzopinacol being particularly suitable. For example, organic peroxides can be obtained from Kayamek RTM A, M, R, L, LH, SP-30C, Perkadox CH-50L, BC-FF, Cadox B-40ES, Perkadox 14, Trigonox RTM 22-70E, 23-C70, 121, 121-50E, 121-LS50E, 21-LS50E, 42, 42LS, Kayaester RTM P-70, TMPO-70, CND-C70, OO-50E, AN, Kayabutyl RTMB. Perkadox 16, Kayacarbon RTM BIC-75, AIC-75 (manufactured by Kayaku Akzo Co., Ltd.), Permek RTM N,H,S,F,D,G,Perhexa RTM H,HC,TMH,C,V,22,MC,Percure RTM AH, AL, HB, Perbutyl RTM H, C, ND, L, Percumyl RTM H.D.Peroyl RTM IB, IPP, Perocta RTM Azo compounds can be obtained from commercial products such as VA-044, V-070, VPE-0201, and VSP-1001 (manufactured by Wako Pure Chemical Industries, Ltd.).
[0117] When a thermal free radical polymerization initiator is used, the content is preferably 0.01 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the total amount of the ultraviolet curable resin. The upper limit of the content of the thermal free radical polymerization initiator is particularly preferably 7 parts by mass, more preferably 5 parts by mass, particularly preferably 4 parts by mass, and most preferably 3 parts by mass. In addition, the lower limit of the thermal free radical polymerization initiator is particularly preferably 0.01 parts by mass, more preferably 0.1 parts by mass, particularly preferably 1 parts by mass, and most preferably 1.5 parts by mass.
[0118] In addition to the above-mentioned components, the barrier layer may be optionally added with leveling agents, defoaming agents, ultraviolet absorbers, light stabilizers, antioxidants, polymerization inhibitors, crosslinking agents, plasticizers, inorganic particles, fillers, etc., to give functions for various purposes. Leveling agents include fluorine compounds, silicone compounds, and acrylic compounds. Ultraviolet absorbers include benzotriazole compounds, diphenyl ketone compounds, and triazine compounds. Light stabilizers include hindered amine compounds and benzoate compounds. Antioxidants include phenol compounds. Polymerization inhibitors include quinone, methylhydroquinone, and hydroquinone. Crosslinking agents include the aforementioned polyisocyanates and melamine compounds. The amount of each of these components added can be appropriately determined according to their purpose.
[0119] The glass transition temperature (Tg) of the barrier layer is preferably 80°C to 300°C, particularly preferably 90°C to 200°C, and even more preferably 150°C to 250°C. The glass transition temperature can be measured, for example, by the DMA method under the following measurement conditions. The measurement is performed using a dynamic viscoelasticity measuring apparatus (DMS-6100: manufactured by SII Nanotechnology) in a tensile mode at a frequency of 10 Hz and a heating temperature of 2°C / min. The loss factor Tanδ is obtained from the ratio of the loss modulus to the storage modulus (JIS: K7244-1: 1998). The temperature at which the obtained loss factor Tanδ becomes the maximum value is set as the glass transition temperature.
[0120] The thickness of the barrier layer is preferably 0.1 μm to 50 μm, particularly preferably 0.5 μm to 20 μm, and more preferably 1 μm to 10 μm. By making the thickness of the barrier layer 0.1 μm or more, when the optical film is applied to the optical laminate described later, it is possible to prevent the phase difference value of the optical functional layer from changing due to the invasion of a plasticizer used as an intermediate film. In addition, by making the thickness of the barrier layer 50 μm or less, the appearance of the optical film during production and the appearance of the functional glass having the optical film during production become excellent. The barrier layer can be obtained by coating the barrier layer-forming resin composition in such a manner that the film thickness after drying is within the above-mentioned preferred range, and curing it by ultraviolet irradiation after drying to form a cured film.
[0121] Examples of the coating method of the barrier layer-forming resin composition include rod coater coating, wire rod coating, air knife coating, gravure coating, reverse gravure coating, micro gravure coating, micro reverse gravure coater coating, die coater coating, dip coating, spin coating, and spray coating.
[0122] The barrier layer having a cured product of a resin composition containing a thermoplastic resin (B-1) and an ultraviolet curable resin (B-2) has excellent adhesion and durability to an interlayer film included in the optical laminate described below. In particular, wrinkles are less likely to occur during the formation of the barrier layer, and in terms of durability, changes in polarization conversion transmittance, hue, and adhesion before and after a heat resistance test are small.
[0123] The resin composition for forming a barrier layer is irradiated with ultraviolet rays for curing, but electron beams or the like may also be used. When curing is performed by ultraviolet rays, the light source may be a xenon lamp, a high-pressure mercury lamp, a metal halide lamp, an LED or the like, and the amount of light, the arrangement of the light source, etc. may be optionally adjusted. When a high-pressure mercury lamp is used, the light source may be irradiated with an ultraviolet ray of 80 to 120 W / cm 2On the other hand, when the barrier layer-forming resin composition is cured by electron beam, it is preferred to use an electron beam accelerator having an energy of 100 to 500 eV. In this case, a photopolymerization initiator may not be used.
[0124] [(C) Support substrate]
[0125] In the optical film of the present invention, when the barrier layer (B) is provided only on one side of the optical functional layer (A), the other side of the optical functional layer is preferably a film-shaped (C) supporting substrate. In order to maintain the viewability of the displayed image, the supporting substrate is preferably transparent in the visible light region. Specifically, the non-polarized light transmittance of a wavelength of 380 to 780 nm is 50% or more, preferably 70% or more, and particularly preferably 85% or more. The so-called non-polarized light transmittance here means the transmittance of light whose vibration is irregular, that is, the transmittance of natural light. In addition, the supporting substrate may be colored, but it is more preferably uncolored or less colored. In addition, the refractive index of the supporting substrate is more preferably 1.2 to 2.0, and more preferably 1.4 to 1.8. The thickness of the supporting substrate can be appropriately selected according to the application, and is more preferably 5μm to 1000μm, more preferably 10μm to 250μm, and particularly preferably 15μm to 150μm.
[0126] (C) The supporting substrate may be a single layer or a laminate of two or more layers. Examples of the supporting substrate include triacetyl cellulose (TAC), acrylic acid, polycarbonate, polyvinyl chloride, polyolefin, and polyethylene terephthalate (PET). Among these, triacetyl cellulose (TAC), polyolefin, and acrylic acid, which have less birefringence, are more preferred in order not to change the polarization axis of the incident P-polarized light or S-polarized light.
[0127] [Method for producing optical film]
[0128] Next, an example of a method for making the optical film of the present invention is described. In this method, for example, a nematic liquid crystal monomer with a polymerizable group, which is a material for making a phase difference element constituting an optical functional layer, is dissolved in a solvent, and then a photopolymerization initiator is added. This solvent is not particularly limited as long as it can dissolve the liquid crystal monomer used, and for example, cyclopentanone, toluene, butanone, methyl isobutyl ketone, etc. can be listed, and cyclopentanone and toluene are more preferred. Then, in a manner that makes the thickness as uniform as possible, the solution is applied to a plastic substrate such as a TAC film used as a supporting substrate, the solvent is removed by heating one side, and the solution is placed on the plastic substrate for a certain period of time under a temperature condition that forms a liquid crystal and is aligned. At this time, by applying a friction treatment to the surface of the plastic substrate to form a desired alignment direction before coating, or by forming a film of a light alignment material that exerts light alignment properties on the surface of the plastic substrate by polarized light irradiation and performing an alignment treatment such as polarized light irradiation, the alignment of the liquid crystal can be made more uniform. According to this, the slow axis of the phase difference element such as the 1 / 2 wavelength plate, the 1 / 4 wavelength plate, the circular polarization reflection layer can be controlled to the desired angle, and the haze value of the phase difference element can be reduced. Then, while maintaining the alignment state, ultraviolet light is irradiated to the nematic liquid crystal monomer by a high-pressure mercury lamp or the like to fix the alignment of the liquid crystal, thereby obtaining a phase difference element with a desired slow axis.
[0129] In the case of a configuration in which the polymerizable liquid crystal monomer is directly coated on the above-mentioned support substrate after the alignment treatment, that is, in the case in which the phase difference element constituting the optical functional layer has a polymerizable liquid crystal layer disposed on the support substrate after the alignment treatment, the support substrate is the same as the barrier layer and has the function of preventing the phase difference value of the phase difference element from decreasing. By making the phase difference element have this configuration, substances that may cause changes in the phase difference value, such as the intermediate film described later, will not directly contact the polymerizable liquid crystal layer of the phase difference element, and as a result, the decrease in the phase difference value of the phase difference element can be suppressed. In addition, compared with the configuration in which a barrier layer is disposed on both sides of the optical functional layer, this configuration can reduce the manufacturing steps of coating one barrier layer, so the optical laminate used in the present invention can be manufactured more cheaply.
[0130] <Optical laminate>
[0131] The optical laminate of the present invention is laminated with an intermediate film on the optical film. The intermediate film is preferably a resin film of a thermoplastic resin, and is particularly preferably a film of polyvinyl butyral. The intermediate film may be one or more sheets, and is preferably an optical laminate having a structure in which the optical film is sandwiched between two intermediate films.
[0132] Figure 4 One embodiment of the optical laminate of the present invention is shown. The optical laminate 20 is formed by sandwiching an optical film 10 between two interlayer films 201. The optical film 10 is equivalent to Figure 3The optical film 10 may be a structure in which the barrier layer is present only on the side where the layer having the function of converting the polarization axis exists in the optical functional layer 101. In this case, the intermediate film 201 only needs to be formed on the barrier layer side, and may also be formed on the supporting substrate side of the 1 / 2 wavelength plate.
[0133] 〈Interlayer film〉
[0134] The interlayer can use thermoplastic resins, and it is more preferred to use generally used automotive interlayers. Examples of such automotive interlayers include polyvinyl butyral resins (PVB: Polyvinyl Butyral), polyvinyl alcohol resins (PVA: Polyvinyl Alcohol), ethylene-vinyl acetate copolymer resins (EVA: Ethylene Vinyl Acetate), or cycloolefin polymers (COP: Cycloolefin Polymer). Interlayers made of these resins are preferred because they can be used as interlayers for laminated glass. In addition, when the optical laminate is applied to the HUD system described later, the thickness of the interlayer is not particularly limited as long as it is within a range that does not affect the reflection of the display light, and can be appropriately designed according to the intended use.
[0135] When the intermediate film for laminated glass is a PVB resin, the phase difference elements such as the 1 / 2 wavelength plate, 1 / 4 wavelength plate, and circularly polarized light reflecting layer composed of polymerizable liquid crystal in contact with the intermediate film deteriorate under high temperature conditions, which sometimes reduces the phase difference value. This can be considered to be the erosion of the PVB resin itself adjacent to the phase difference element, the influence of the plasticizer contained in the PVB resin, etc. In the optical laminate of the present invention, even if the intermediate film made of this PVB resin or the intermediate film made of PVB resin containing a plasticizer is directly in contact with the optical film and laminated, the degradation of the phase difference elements such as the 1 / 2 wavelength plate, the 1 / 4 wavelength plate, and the circularly polarized light reflecting layer can be suppressed, and the change of the phase difference value can also be suppressed.
[0136] Plasticizers for reducing the phase difference value of the phase difference element composed of polymerizable liquid crystals include, for example, organic ester plasticizers such as monobasic organic acid esters and polybasic organic acid esters, or organic phosphoric acid plasticizers such as organic phosphoric acid and organic phosphorous acid. Examples of the above-mentioned monobasic organic acid esters include: glycol esters obtained by reacting diols such as triethylene glycol, tetraethylene glycol, and tripropylene glycol with monobasic organic acids such as butyric acid, isobutyric acid, hexanoic acid, 2-ethylbutyric acid, heptanoic acid, n-octanoic acid, 2-ethylhexanoic acid, geranic acid (n-nonanoic acid), and decanoic acid.
[0137] Examples of the polybasic organic acid esters include ester compounds of polybasic organic acids such as adipic acid, sebacic acid, and azelaic acid, and alcohols having a linear or branched structure and having 4 to 8 carbon atoms.
[0138] Examples of the organic ester plasticizer include triethylene glycol-di-2-ethylbutyrate, triethylene glycol-di-2-ethylhexanoate, triethylene glycol dioctanoate, triethylene glycol-di-n-octanoate, triethylene glycol-di-n-heptanoate, tetraethylene glycol-di-2-ethylhexanoate, tetraethylene glycol-di-n-heptanoate, dibutyl sebacate, dioctyl azelate, dibutyl carbitol adipate, ethylene glycol-di-2-ethylbutyrate, 1,3-propylene glycol-di-2-ethylbutyrate, 1,4-butylene glycol-di-2-ethylbutyrate, diethylene glycol-di-2-ethylbutyrate, diethylene glycol-di-2-ethylbutyrate, and diethylene glycol-di-2-ethylbutyrate. Diol-di-2-ethylhexanoate, dipropylene glycol-di-2-ethylbutyrate, triethylene glycol-di-2-ethylvalerate, tetraethylene glycol-di-2-ethylbutyrate, diethylene glycol dioctanoate, triethylene glycol-di-n-heptanoate, tetraethylene glycol-di-n-heptanoate, triethylene glycol diheptanoate, tetraethylene glycol diheptanoate, dihexyl adipate, dioctyl adipate, hexylcyclohexyl adipate, a mixture of heptyl adipate and nonyl adipate, diisononyl adipate, heptyl nonyl adipate, dibutyl sebacate, oil-modified sebacic acid alkyd resin, a mixture of phosphate ester and adipic acid ester, etc.
[0139] Examples of the organic phosphoric acid plasticizer include tributoxyethyl phosphate, isodecylphenyl phosphate, and triisopropyl phosphate.
[0140] Ultraviolet absorbers, antioxidants, antistatic agents, heat stabilizers, colorants, bonding regulators, etc. can be appropriately added to the interlayer for laminated glass. In particular, the interlayer dispersed with infrared absorbing particles is important for making high-performance heat-insulating laminated glass. Infrared absorbing particles are particles of conductive materials such as metals such as Sn, Ti, Zn, Fe, Al, Co, Ce, Cs, In, Ni, Ag, Cu, Pt, Mn, Ta, W, V, and Mo, oxides of the metals, nitrides of the metals, or composites containing at least two of these. In addition, Sn, Sb, F, etc. can also be doped in these materials. In particular, tin-doped indium oxide (ITO: Indium Tin Oxide), antimony-doped tin oxide (ATO: Antimony Tin Oxide), and fluorine-doped tin oxide, which are transparent in the visible light region, are preferred when using laminated glass as windows for buildings and automobiles that require transparency. The particle size of the infrared absorbing microparticles dispersed in the intermediate film is preferably 0.2 μm or less. If the particle size of the microparticles is 0.2 μm or less, the scattering of light in the visible light region can be suppressed and infrared rays can be absorbed. The laminated glass will not fog and radio wave permeability and transparency can be ensured. The physical properties such as bonding, transparency, and durability are maintained on an equal basis with those of the intermediate film without addition, and the laminated glass can be vitrified in the operation of a normal laminated glass manufacturing line. In the case of using PVB resin for the intermediate film, in order to most appropriately maintain the moisture content of the intermediate film, the lamination process is performed in a constant temperature and humidity room. In addition, the intermediate film can be used to form a sandwich structure by coloring a portion, sandwiching a layer with a sound insulation function, and to reduce the ghosting phenomenon (double image) in the HUD so that the thickness has a slope (wedge shape), etc.
[0141] There is no particular limitation on the method of laminating the intermediate film for laminated glass and the optical film having an optical functional layer such as a half-wave plate or a quarter-wave plate. For example, a method of laminating the intermediate film and the optical film by synchronously pressing the intermediate film and the optical film using a roller can be cited. In the case where the roller can be heated during lamination, it is also possible to press the intermediate film and the optical film while heating them. In addition, in the case where the adhesion between the intermediate film and the optical film is poor, the intermediate film and the optical film can be laminated after surface treatment such as corona treatment or plasma treatment in advance.
[0142] The intermediate film can also be directly laminated on one or both sides of the optical film in a state of being dissolved in a solvent. When a polyvinyl butyral resin (PVB) is used as the intermediate film, the butyralization degree is preferably 40 mol% or more and 85 mol% or less, and the lower limit of the butyralization degree is preferably 55 mol%, and particularly preferably 60 mol%. On the other hand, the upper limit of the butyralization degree is preferably 80 mol%, and particularly preferably 75 mol%. The butyralization degree can be measured by infrared absorption spectroscopy (IR), for example, FT-IR can be used to measure.
[0143] The hydroxyl content of the polyvinyl butyral resin is preferably 15 mol% or more and 35 mol% or less. When the hydroxyl content is less than 15 mol%, the bonding between the interlayer film for laminated glass and the glass may be reduced or the penetration resistance of the laminated glass may be reduced. On the other hand, when the hydroxyl content exceeds 35 mol%, the interlayer film may become hard.
[0144] Polyvinyl butyral resin can be prepared by acetalizing polyvinyl alcohol with aldehyde. Polyvinyl alcohol can be generally obtained by saponifying polyvinyl acetate, and polyvinyl alcohol having a saponification degree of 80 to 99.8 mol % is generally used. In addition, the degree of polymerization of polyvinyl alcohol is preferably 4000 or less, particularly preferably 3000 or less, and particularly preferably 2500 or less. When the degree of polymerization exceeds 4000, the intermediate film is sometimes difficult to form.
[0145] 〈Functional glass〉
[0146] The functional glass of the present invention comprises the above-mentioned optical laminate and a glass plate. The glass plate may be one or more, and preferably is a functional glass having a structure in which the optical laminate is sandwiched between two glass plates. This functional glass is preferably used as a display medium in a HUD system.
[0147] Functional glass can be produced, for example, by bonding the optical laminate to a glass plate. One example of a method of bonding an optical laminate to a glass plate is to apply an adhesive or bonding agent to one or both sides of the optical laminate and then bond the glass plate. The adhesive or bonding agent is not particularly limited. In the case where it may be peeled off later, a material with excellent reworkability and preferred adhesion is more preferred, such as a silicone adhesive or an acrylic adhesive.
[0148] The glass plate is not particularly limited as long as it has transparency that allows the scenery ahead to be fully viewed even when the functional glass of the present invention is used as a windshield. In addition, the refractive index of the glass plate is preferably 1.2 to 2.0, and particularly preferably 1.4 to 1.8. In addition, the thickness, shape, etc. of the glass plate are not particularly limited as long as they are within the range that will not affect the reflection of the display light when the functional glass is applied to the HUD system described later, and can be appropriately designed according to the application. In addition, on the glass plate, an enhanced reflective film composed of a multilayer film, or a metal film that also has a heat insulation function, etc. can be provided on the reflective surface. These films can increase the reflectivity of the incident polarized light, but in the case of using the functional glass of the present invention as a windshield for an automobile, for example, it is more preferred to adjust the reflectivity in such a way that the visible light transmittance of the functional glass becomes 70% or more.
[0149] When the optical layered body of the present invention is used, the optical layered body is disposed between two glass plates and pressure-bonded at high temperature and high pressure, thereby obtaining a functional glass in which the optical layered body is disposed in a laminated glass. Figure 5 An embodiment of the functional glass according to the present invention is presented. Figure 5 The functional glass 30 shown is formed by two glass plates 301, and the optical laminate 20 is sandwiched therebetween. The optical laminate 20 corresponds to, for example, Figure 4 An optical laminate. Figure 3 As shown, the optical film 10 constituting the optical laminate 20 has a barrier layer 102 on one side of the optical functional layer 101, and the other side may be a supporting substrate (not shown in the figure), or the barrier layer 102 may be provided on both sides of the optical functional layer 101. Figure 5 As shown, when the optical laminate 20 constitutes the functional glass 30 , the intermediate film 201 also has a function as an adhesive or bonding agent for maintaining the adhesion between the two glass plates 301 and the optical laminate 20 .
[0150] Next, an example of a method for making functional glass using the optical film of the present invention is specifically described. First, two glass plates are prepared. In the case of using laminated glass for automobile windshields, soda-lime glass made by a float process is used. The glass can be transparent or tinted green, without any particular restrictions. The thickness of these glass plates is usually about 2 mmt, but in recent years, glass plates with a thickness slightly thinner than this can also be used in response to the demand for lightweight glass. The glass plate is cut into a predetermined shape, and the glass edge is cross-sectioned and washed. When a black frame or dot shape is required, this is printed on the glass plate. In the case of a curved surface shape required like a windshield, the glass plate is heated to above 650°C, and then shaped in a manner such that the two sheets have the same surface shape by molding or bending according to its own weight, and the glass is cooled. At this time, if the cooling speed is too fast, the glass plate will produce stress distribution and become a tempered glass, so slow cooling is performed. One of the glass plates made in this way is placed horizontally, the optical film of the present invention is overlapped on it, and then another glass plate is placed. Or a method of sequentially stacking an intermediate film, an optical film, and an intermediate film on top of a glass plate, and finally placing another glass plate. At this time, in the optical film, the phase difference element as an optical functional layer is arranged in a manner to become the outer side of the vehicle. Then, the optical film and the intermediate film protruding from the edge of the glass plate are cut and removed by a cutter. Then, while degassing the air between the glass plates, intermediate films, and optical films stacked in a sandwich shape, the temperature is heated from 80°C to 100°C for pre-bonding. There are two methods for degassing the air: a bag method in which a laminate of glass plates / intermediate films / optical films / intermediate films / glass plates is packaged in a rubber bag formed by heat-resistant rubber, etc., and a ring method in which a rubber ring is used to seal only the end of the glass. Either method can be used. After the pre-bonding is completed, the laminate of glass plates / intermediate films / optical films / intermediate films / glass plates taken out of the rubber bag or the laminate after the rubber ring is removed is placed in an autoclave and heated at 10 to 15 kg / cm 2 The autoclave is heated to 120°C to 150°C under high pressure and subjected to heat and pressure treatment for 20 minutes to 40 minutes. After the treatment, the autoclave is cooled to below 50°C and the pressure is released, and the functional glass of the present invention consisting of glass / intermediate film / optical film / intermediate film / glass is taken out from the autoclave.
[0151] In addition, in the above-mentioned embodiment, the intermediate film is arranged as a single independent film overlapped between the glass plate and the optical film, but instead, the intermediate film may be arranged in a state of being directly laminated on the optical film in advance, that is, in a state of an optical laminate. Specifically, the intermediate film of at least one of the two intermediate films may be an optical laminate directly laminated on the optical film in advance. By using this intermediate film, the step of arranging the intermediate film between the optical film and the glass plate can be omitted, and as a result, the manufacturing cost can be reduced.
[0152] The functional glass obtained in this way can be used as windshield, side windshield, rear windshield, and roof glass not only in ordinary cars, small cars, and light cars, but also in large special cars and small special cars. In addition, it can also be used as windows for railway cars, ships, and airplanes, as well as window materials for building materials and industrial use. Regarding the usage form, it can also be used by laminating or bonding with components with UV cutoff or dimming functions.
[0153] 〈Head-up display system〉
[0154] The optical film of the present invention is excellent in adhesion and appearance when laminated glass is formed using the optical film, and therefore is suitable for use in a head-up display system. Figure 1 One embodiment of a HUD system in accordance with the present invention is presented. Figure 1 The HUD system shown in the figure comprises: a display 2 that makes the display light presenting the display image become P-polarized light and emits it, a reflector 3 that reflects the display light emitted from the display 2, and the functional glass 4 of the present invention on which the P-polarized light or S-polarized light emitted from the display 2 is incident. The P-polarized light or S-polarized light emitted from the display 2 is reflected by the reflector 3, and the reflected display light is irradiated on the functional glass 4 of the present invention that functions as a windshield, thereby the P-polarized light or S-polarized light reaches the observer 1 via the optical path 5, and the observer can view the display image 6 as a virtual image. Figure 1 In the HUD system shown, the display light emitted from the display 2 is incident on the functional glass 4 via the reflector 3 , but the display light may be directly incident on the functional glass 4 from the display 2 .
[0155] <monitor>
[0156] The display 2 is not particularly limited as long as it can emit the desired P-polarized light or S-polarized light before finally reaching the functional glass 4. Examples thereof include a liquid crystal display (LCD) and an organic EL display (OELD). In the case where the display 2 is a liquid crystal display, the emitted light is usually linearly polarized and can be used directly. On the other hand, in the case where the display 2 is an organic EL display, Figure 2As shown, the display 2 may be composed of, for example, a light source 2A and a polarizing plate 2B that can emit P polarized light or S polarized light. In addition, when the HUD system is used in a car, the liquid crystal display device and the organic EL display may also be configured with optical components such as a polarizing plate and a 1 / 2 wavelength plate on a light outlet such as a dashboard, and adjusted in a manner that P polarized light or S polarized light can be emitted from the display 2. In addition, the light source used in the display 2 is not particularly limited, and a laser light source or an LED light source may be used. In addition, the central reflection wavelength of the phase difference element constituting the optical functional layer is set in a manner corresponding to the luminous spectrum of the above-mentioned light source, thereby making the displayed image clearer more effectively.
[0157] In the HUD system of the present invention, when the display light emitted from the display 2 is P polarized light and the Brewster angle of the P polarized light relative to the functional glass is set to α, the incident angle of the P polarized light incident on the functional glass 4 is preferably in the range of α-10° or more and α+10° or less. That is, the P polarized light from the display 2 is incident on the functional glass 4 at an incident angle near the Brewster angle, thereby greatly reducing the reflection of the P polarized light on the surface of the glass plate of the functional glass 4. In the optical laminate constituting the functional glass 4, when an optical film having a 1 / 2 wavelength plate is used as the optical functional layer, the P polarized light after penetrating the glass plate is converted into S polarized light by the 1 / 2 wavelength plate constituting the optical functional layer, and the converted S polarized light is reflected at the interface of the other glass plate. The reflected S polarized light is converted into P polarized light again by the 1 / 2 wavelength plate, and this P polarized light reaches the observer. Accordingly, the observer can view the displayed image as a virtual image. On the other hand, when the incident angle of the P polarized light is less than α-10° or greater than α+10°, the incident angle of the P polarized light deviates from the vicinity of the Brouster angle, so the reflectivity of the P polarized light increases, and sometimes double images are generated. In this way, by adjusting the incident angle of the P polarized light to near the Brouster angle, the generation of double images can be greatly reduced. In addition, since the reflected light from the road surface is generally S polarized light, observers sometimes use polarized sunglasses. Since polarized sunglasses are designed to absorb S polarized light, in previous HUD systems that use S polarized light, the visibility of the displayed image of the HUD through the polarized sunglasses is extremely reduced. On the other hand, if the P polarized light is allowed to reach the observer's HUD system using P polarized light, the generation of double images can be suppressed, and the visibility of the displayed image can also be improved when wearing polarized sunglasses.
[0158] <Reflector>
[0159] The HUD system of the present invention may optionally include a reflector. The reflector is not particularly limited as long as it can reflect the display light from the display toward the optical laminate, and may be composed of, for example, a plane mirror, a concave mirror, etc. When a concave mirror is used as a reflector, the concave mirror can also amplify the display light from the display at a predetermined magnification ratio.
[0160] [Example]
[0161] The present invention is described in detail below by way of examples. The present invention is not limited to the following examples without exceeding the scope of the present invention, and in the examples, "parts" means parts by mass.
[0162] [Example 1]
[0163] <Preparation of coating liquid (liquid crystal composition)>
[0164] A coating solution A having the composition shown in Table 1 was prepared.
[0165] [Table 1]
[0166] Material(type) Material Name (Manufacturer) Mixing quantity (serving) Polymerized Liquid Crystal LC242 (BASF) 25.0 Photopolymerization initiator Irgacure 907 (BASF) 1.0 Solvents Toluene 74.0
[0167] <Preparation of UV Curable Resin Coating Liquid for Barrier Layer Formation>
[0168] A coating liquid B of an ultraviolet curable resin composition (resin composition for forming a barrier layer) having a composition shown in Table 2 was prepared.
[0169] [Table 2]
[0170] Material(type) Material Name (Manufacturer) Mixing quantity (serving) (B-2) Ultraviolet curable resin PET30 (Nippon Kayaku Co., Ltd.) 25.7 (B-1) Thermoplastic resin KS-10 (Sekisui Chemical Co., Ltd.) 2.9 Photopolymerization initiator Irgacure 907 (BASF) 1.5 Solvents Butanone 70.0
[0171] <Production of optical film>
[0172] Optical films were prepared using the prepared coating liquid A according to the following procedure: As a plastic substrate of the supporting substrate, a TAC film (thickness 80 μm) previously rubbed by the method described in Example 1 of Japanese Patent Application Laid-Open No. 2002-90743 was used.
[0173] (1) Using a wire bar, the coating liquid A was applied to the rubbed surface of the TAC film at room temperature so that the thickness of the half-wavelength plate as the optical functional layer obtained after drying would be 2 μm.
[0174] (2) The obtained coating film was heated at 50°C for 2 minutes to remove the solvent and form a liquid crystal phase. Then, UV was irradiated for 5 to 10 seconds using a high pressure mercury lamp (manufactured by Harrison Toshiba Lighting Co., Ltd.) at an output of 120 W to fix the liquid crystal phase, thereby producing a 1 / 2 wavelength plate having a polymerizable liquid crystal layer laminated on a TAC film.
[0175] (3) Using a wire bar, coating liquid B, which is a barrier layer-forming resin composition, was applied to the polymerizable liquid crystal layer side of the half-wavelength plate at room temperature so that the thickness of each barrier layer obtained after drying would be 3.0 μm.
[0176] (4) The obtained coating film is heated at 80°C for 1 minute to remove the solvent, and then a high-pressure mercury lamp (manufactured by Harrison Toshiba Lighting Co., Ltd.) is used to irradiate UV for 5 to 10 seconds at an output of 120 W, and the barrier layer is laminated on the polymerizable liquid crystal layer side of the 1 / 2 wavelength plate. In this way, an optical film having a barrier layer on one side of the 1 / 2 wavelength plate and a supporting substrate (TAC film) on one side of the 1 / 2 wavelength plate is produced. The obtained optical film is placed between polarizing plates arranged in parallel, and the transmittance during polarization conversion is measured by the "Ultraviolet Visible Near Infrared Spectrophotometer UV-3600" manufactured by Shimadzu Corporation, and then the wavelength at which the transmittance becomes the minimum, that is, the wavelength at which the polarization conversion (performance) becomes the maximum, is measured. The result after the measurement is that the wavelength at which the polarization conversion (performance) of the optical film becomes the maximum is 545nm.
[0177] <Production of Optical Laminated Body>
[0178] Two transparent interlayer films made of polyvinyl butyral resin with a thickness of 0.38 mm and containing triethylene glycol di-2-ethylhexanoate as a plasticizer were used, and the optical film was placed between the interlayer films of the polyvinyl butyral film. The optical film and the two interlayer films were then pressed and bonded by a laminator to produce an optical laminate.
[0179] 〈Production of functional glass〉
[0180] The produced optical laminate was placed between two glass plates each having a thickness of 2 mm, and heated under pressure by the following method to produce functional glass.
[0181] First, the optical laminate and the transparent glass plate are stacked on the transparent glass plate. Then, the excess part of the optical laminate protruding from the edge of the glass plate is cut off and removed. The optical laminate is packaged in a rubber bag and degassed in an autoclave heated to 90°C for 10 minutes for pre-bonding. The pre-bonded optical laminate is cooled to room temperature, then taken out of the rubber bag and placed in the autoclave again at 135°C and 12kg / cm 2 The glass was heated and pressurized for 30 minutes under high pressure. In this way, a functional glass with good appearance was produced. The total light transmittance of the produced functional glass was measured and the result was 89.5%, showing excellent transmittance. The total light transmittance was measured using a fully automatic haze meter "TC-HIIIDPK" manufactured by Tokyo Denshoku Co., Ltd. in accordance with JIS standard K7105.
[0182] [Examples 2 to 8, Comparative Examples 1 to 3]
[0183] The optical films, optical laminates and functional glasses of Examples 2 to 8 and Comparative Examples 1 to 3 were produced by the same operation as in Example 1, except that the (B-1) thermoplastic resin in Table 2 was changed to the thermoplastic resin shown in Table 3. Comparative Example 1 did not have a barrier layer, and Comparative Examples 2 and 3 did not have a thermoplastic resin in the barrier layer. The functional glass of Comparative Example 3 was subjected to the same operation as in Example 1, and the total light transmittance was measured, which was 88.5%.
[0184] The properties of the optical films and functional glasses of Examples 1 to 8 and Comparative Examples 1 to 3 were measured and evaluated in the following manner.
[0185] 〈Wavelength shift due to autoclave processing〉
[0186] The minimum wavelength in polarization conversion when making functional glass from an optical film was measured, and the difference was calculated as the wavelength shift amount S1 (nm) formed by autoclave processing. The results are shown in Table 3. The wavelength shift amount S1 (nm) formed by autoclave processing is a value obtained by the following formula.
[0187] S1 = Minimum wavelength of polarization conversion of functional glass (nm) – Minimum wavelength of polarization conversion of optical film (nm)
[0188] 〈Heat resistance evaluation〉
[0189] The functional glasses obtained in the examples and comparative examples were placed in a high temperature environment of 120°C for 1200 hours, and the wavelength shift before and after the placement was measured. The results are shown in Table 3. The wavelength shift amount S2 (nm) formed by the durability test, which shows the degree of change in the phase difference value, is a value obtained by the following formula.
[0190] S2 = wavelength of functional glass after input (nm) – wavelength of functional glass before input (nm)
[0191] 〈Hue change (ΔE)〉
[0192] In the C region, the test pieces for measuring the optical films of Examples 1 to 8 and Comparative Examples 1 to 3 were cut out in a size of 50 mm × 50 mm, and the test pieces were set so that the normal line of the film plane coincided with the incident light using a spectrophotometer CM-3600A manufactured by Konica Minolta, and the chromaticity a*, chromaticity b*, and lightness L* at any point on the test piece were measured by transmitted light under the condition of a target mask with a measurement diameter of Φ8 mm. Then, the test piece was moved so as to be spaced at least 20 mm from the center of the measurement point, and the same measurement was repeated 4 times, and the chromaticity a*, chromaticity b*, and lightness L* of the C region were respectively set as a*C, b*C, and L*C from the average values of the five times. The same measurement was also performed on the E region, and the chromaticity a*, chromaticity b*, and lightness L* of the E region were respectively set as a*E, b*E, and L*E from the average values of the five times. The hue change ΔE was calculated using formulas (V) to (VIII) and the combination of chromaticity a*, chromaticity b*, and lightness L* in the C region and the E region. The obtained hue change ΔE results are shown in Table 3. The hue change test was performed using a heat-resistant acceleration tester under 100°C-dry conditions for 1200 hours.
[0193] ΔL*=L*CL*E···(V)
[0194] Δa*=a*Ca*E···(VI)
[0195] Δb*=b*Cb*E···(VII)
[0196] ΔE*=((ΔL*) 2 +(Δa*) 2 +(Δb*) 2 ) 1 / 2 ···(VIII)
[0197] <Measurement of haze>
[0198] The functional glass was measured and evaluated by a haze meter. The results are shown in Table 3.
[0199] 〈Adhesion〉
[0200] Adhesion is evaluated by the Pummel test. Specifically, after the functional glass is placed in a freezer at a temperature of -18°C ± 0.6°C for 16 hours, the central part of the functional glass (a part of 150 mm in length × 150 mm in width) is hit with a hammer with a hammer head of 0.45 kg, and the glass is crushed until the particle size becomes less than 6 mm. The exposure of the barrier layer after the glass is partially peeled off is determined by the Pummel value. From the obtained Pummel value, the following criteria are used for evaluation, and "△" or above is considered qualified. The results are shown in Table 3.
[0201] ○: No peeling
[0202] △: There is no peeling after hitting with a hammer, but peeling occurs when peeling with hands
[0203] ×: Peeling occurs after hitting with a hammer
[0204] 〈Light Distortion〉
[0205] The presence or absence of light distortion observed when observing through the functional glass and when reflecting light was evaluated visually. No distortion was observed in the image and evaluated as "○", only slight distortion was observed in the image and evaluated as "△", distortion was observed in the image and evaluated as "×", and "△" or above was considered as passing. The results are shown in Table 3.
[0206] [Table 3]
[0207]
[0208] ·KS-10: Polyvinyl acetal resin (manufactured by Sekisui Chemical Co., Ltd., product name "S-LEC KS-10")
[0209] BL-1: Polyvinyl butyral resin (manufactured by Sekisui Chemical Co., Ltd., product name "S-LEC BL-1")
[0210] BM-S: Polyvinyl butyral resin (manufactured by Sekisui Chemical Co., Ltd., product name "S-LEC BM-S")
[0211] BL-S: Polyvinyl butyral resin (manufactured by Sekisui Chemical Co., Ltd., product name "S-LEC BL-S")
[0212] MD-1480: Polyester resin (manufactured by Toyobo Co., Ltd., product name "Vylonal MD-1480")
[0213] MD-2000: Polyester resin (manufactured by Toyobo Co., Ltd., product name "Vylonal MD-2000")
[0214] UR-1700: Polyester urethane resin (manufactured by Toyobo Co., Ltd., product name "Vylon UR1700")
[0215] ·LIR-403: Isoprene resin (manufactured by Kuraray Co., Ltd., product name "Kuraprene LIR-403")
[0216] PET30: Pentaerythritol triacrylate (manufactured by Nippon Kayaku Co., Ltd., product name "KAYARAD PET30")
[0217] UX-4101: Urethane resin (manufactured by Nippon Kayaku Co., Ltd., product name "KAYARAD UX-4101")
[0218] From Table 3, it can be seen that the functional glasses prepared in Examples 1 to 8 having a barrier layer containing a thermoplastic resin show excellent characteristics in the wavelength shift S1 during autoclave processing, the wavelength shift S2 formed according to the durability test, and the color phase change ΔE, compared with the functional glasses prepared in Comparative Examples 1 to 3. Therefore, in Examples 1 to 8, an optical film with high durability and capable of suppressing the change in the phase difference value of the phase difference element for a long time in a high temperature environment can be provided.
[0219] On the other hand, the functional glass produced in Comparative Example 1 without a barrier layer had a large wavelength shift S1 during autoclave processing and a large wavelength shift S2 according to the durability test, and was inferior in durability and optical performance under high temperature environments. In addition, peeling was observed between the barrier layer and the PVB layer in the adhesion test.
[0220] In the functional glasses produced in Comparative Examples 2 and 3, which do not contain thermoplastic resin in the barrier layer, the wavelength shift S1 during autoclave processing and the wavelength shift S2 formed by the durability test were also large, and the durability and optical performance in a high temperature environment were poor. In addition, distortion was also observed in the image in the optical distortion evaluation.
[0221] Thus, the present invention can provide an optical film that maintains high visible light transmittance on one side and effectively improves the reflectance of only specific polarized light, has high durability, and can suppress the change of phase difference value for a long time, as well as an optical laminate, functional glass and head-up display system using the optical film. In addition, the barrier layer used in the optical film of the present invention is easy to laminate with the optical functional layer such as the above-mentioned phase difference element, and has excellent workability, so it is very practical.
[0222] Description of Reference Numerals
[0223] 1 Observer
[0224] 2 Display
[0225] 2A Light Source
[0226] 2B polarizing plate
[0227] 3 Reflector
[0228] 4 Functional glass
[0229] 5 Light Path
[0230] 6 Displaying images
[0231] 10 Optical film
[0232] 101 Optical Functional Layer
[0233] 102 Barrier layer
[0234] 20 Optical laminate
[0235] 201 Intermediate film
[0236] 30 Functional glass
[0237] 301 Glass plate.
Claims
1. An optical film comprising (A) an optical functional layer and (B) a barrier layer, The barrier layer (B) comprises: a cured product of a resin composition containing a (B-1) thermoplastic resin and a (B-2) ultraviolet curable resin, The aforementioned (B-1) thermoplastic resin is a polyvinyl acetal resin, The (B-2) ultraviolet curable resin is a resin having a (meth)acryloyl group. 2 . The optical film according to claim 1 , wherein the thermoplastic resin (B-1) is a thermoplastic resin having a molecular weight of 10,000 to 60,000. 3 . The optical film according to claim 1 , wherein the thermoplastic resin (B-1) is a polyvinyl acetal resin. 4 . The optical film according to claim 1 , wherein the content of the thermoplastic resin (B-1) in the barrier layer is 1% by mass or more and 80% by mass or less. 5 . The optical film according to claim 1 , wherein the resin having a (meth)acryloyl group is a (meth)acrylate epoxy resin. 6 . The optical film according to claim 1 , wherein the glass transition temperature of the barrier layer (B) is 80° C. or higher and 300° C. or lower.
7. The optical film according to claim 1 or 2, wherein the aforementioned (A) optical functional layer is any one of the following (A-1) to (A-4), (A-1) 1 / 2 wavelength plate, (A-2) 1 / 4 wavelength plate, (A-3) A laminate of a half-wavelength plate and a circularly polarized light reflecting layer, and (A-4) A laminate of a quarter-wave plate and a circularly polarized light reflecting layer. 8 . The optical film according to claim 7 , wherein the half-wavelength plate or the quarter-wavelength plate includes a polymerizable liquid crystal layer as a layer having a function of converting a polarization axis. 9 . The optical film according to claim 1 , further comprising (C) a supporting substrate. 10 . An optical laminate comprising the optical film according to claim 1 and an interlayer film laminated thereon. 11 . A functional glass comprising the optical layered body according to claim 10 and a glass plate.
12. A head-up display system comprising: the optical film according to any one of claims 1 to 9, the optical layered body according to claim 10, or the functional glass according to claim 11, and an image display unit that emits display light for presenting an image display.
Citation Information
Patent Citations
Display device
JP1994040271A
Method for rubbing
JP2002090743A
Polarizing plate with optical compensation function and liquid crystal display device using the same
JP2003315556A
Method for manufacturing film comprising polymerized liquid crystal material
JP2004029824A
Light reflection film, and optical film using the same, functional glass, and head-up display
JP2017198981A